2009
DOI: 10.1021/np8006364
|View full text |Cite
|
Sign up to set email alerts
|

Benzophenone Derivatives from the Fruits of Garcinia multiflora and Their Anti-inflammatory Activity

Abstract: Five new benzophenone derivatives, 13,14-didehydoxyisogarcinol (1), garcimultiflorone A (2), garcimultiflorone B (3), 13-hydroxygarcimultiflorone B (4), and garcimultiflorone C (5), have been isolated from the fruits of Garcinia multiflora, together with seven known compounds (6-12). The structures of these new compounds were determined through spectroscopic and MS analyses. 13,14-Didehydoxyisogarcinol (1), garcimultiflorone A (2), garcimultiflorone B (3), and 13-hydroxygarcimultiflorone B (4) exhibited inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 20 publications
0
45
0
Order By: Relevance
“…For example, benzophenone and phloroglucinol derivatives isolated from the fruits of Garcinia multiflora [183185] and seeds of Garcinia subelliptica [186, 187] inhibited f MLF-induced responses, with the most potent being garcimultiflorone B (Table 1). Several phthalides isolated from Pittosporum illicioides had weak inhibitory activity on f MLF-induced O 2 −· production and HNE release by neutrophils [188].…”
Section: Small-molecule Non-peptide Fpr1 Antagonists and Their Synmentioning
confidence: 99%
“…For example, benzophenone and phloroglucinol derivatives isolated from the fruits of Garcinia multiflora [183185] and seeds of Garcinia subelliptica [186, 187] inhibited f MLF-induced responses, with the most potent being garcimultiflorone B (Table 1). Several phthalides isolated from Pittosporum illicioides had weak inhibitory activity on f MLF-induced O 2 −· production and HNE release by neutrophils [188].…”
Section: Small-molecule Non-peptide Fpr1 Antagonists and Their Synmentioning
confidence: 99%
“…Its fruits are edible consisting of vitamins, proteins, and minerals, but may also provide pharmacologically active compounds. 5 Previous phytochemical investigations on the fruits led to isolation of seven new PPAPs with anti-inammatory activity, including two caged PPAPs garcimultiorone D and G. [6][7][8] Taken together, these results prompted us to investigate the isolation of further caged PPAPs form G. multiora and evaluate their biological activities. As a result, nine undescribed caged polycyclic polyprenylated acylphloroglucinols (PPAPs), including adamantane type PPAPs (1-2) and homoadamantane type PPAPs (3)(4)(5)(6)(7)(8)(9) were isolated from the fruits of G. multiora, along with three known analogues.…”
Section: Introductionmentioning
confidence: 99%
“…585.35745). Detailed analysis of the 1D and 2D NMR spectra indicated that compound 2 featured a unique caged tetracyclo-[6.3.1.1 3,10 .0 3,7 ]tridecane skeleton which was the same as those of hyperisampsins A-D. 10 Comparison of the 13 C NMR data of 2 with that of hyperisampsin C revealed that two compounds were similar except for the presence of an isogeranyl group at C-5 in 2 instead of a geranyl group in hyperisampsin C. The constitution of 2 was conrmed by HMBC correlations between H 2 -22 and C-5 (d C 68.2) and C-9 (d C 201.9). The relative conguration of 2 was established as the same that of hyperisampsin C by ROESY spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…7 Apart from this single report, however, no additional information on the biological activities of natural products 5 and 6 exist further emphasizing the need for an efficient and scalable synthetic route to this class. Although studies have reported the importance of 13,14-hydroxyls with regard to isogarcinol’s histone acetyltransferase (HAT) inhibition and radical-scavenging abilities, 2a,6,8c,d,11e biological data on analogs that lack the hydroxyl functionalities (e.g., 5 and 6 ) are limited.…”
Section: Introductionmentioning
confidence: 99%